Internal Control Of Multi-Purpose Credit Granting: Case Study Of Bank Xyz In Indonesia - Luluk Dwi Widyawati; Efendri Efendri; Ludwina Harahap (Information Technology and Science (ITScience), 2025)
This research aims to analyze internal control in the provision of Multi-Purpose Credit (KSM) at Bank XYZ Branch XX. The primary focus of this study is to understand how control activities can minimize credit risk faced by the bank. Credit risk refers to the potential loss incurred by lenders due to borrowers failing to meet their obligations as per the agreed terms. In this context, effective internal control is crucial to ensure that all aspects of credit provision are carried out accurately and properly. Control activities encompass a series of procedures and policies designed to manage credit risk, including application processes, document review, risk assessment, credit approval, and periodic monitoring of credit after disbursement. Multi-Purpose Credit is an unsecured product offered to permanent employees with a maximum loan limit of IDR 1,500,000,000 and a maximum tenor of 15 years. This study also explores the actions taken by the bank against employees who violate SOPs in the provision of KSM. By utilizing qualitative analysis methods, this research is expected to provide deeper insights into the effectiveness of internal control in credit provision, as well as recommendations for improving the existing control systems. The findings of this research are anticipated to serve as a reference for the bank in enhancing the quality of credit control and reducing potential risks in the future.